2019
DOI: 10.1027/2512-8442/a000032
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Coping in Foster and Biological Parents and Its Relation to Child Psychopathology

Abstract: Abstract. This study investigated whether foster parents’ reports of their dyadic coping competencies differ from biological parents, whether there are differences with regard to the temporal associations between maternal and paternal dyadic coping in the two samples, and whether parental dyadic coping competencies predict future mental health problems in children. A total of 94 foster children and 157 children living in their biological families, both samples aged 2–7 years, as well as their (foster) parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Interestingly, when looking at the relation between DC and child outcomes, no associations between DC and child mental health was found nor were child mental health problems prospectively predicted by parental DC (Job et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, when looking at the relation between DC and child outcomes, no associations between DC and child mental health was found nor were child mental health problems prospectively predicted by parental DC (Job et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Only few studies in the current review have taken child outcomes into account (Job et al, 2019; Körner et al, 2013; Zemp et al, 2019). In some studies, DC was not related to child outcomes, like child metabolic control when dealing with diabetes (Körner et al, 2013) or child mental health (internalizing and externalizing behavior; Job et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample consisted of 94 children living in foster and 157 children living in their biological families (e.g. [49][50][51]). In total, 251 parents (mostly mothers) reported about their child (in foster care) completing the PAS.…”
Section: Participantsmentioning
confidence: 99%
“…A large body of literature found that parental negativity is associated with more child mental health problems (Cummings & Davies, 2010;Giallo et al, 2021), but the role of positive interparental interactions (i.e., dyadic coping [DC]) in promoting child well-being has been investigated more recently (Job et al, 2019;Skinner et al, 2021;Zemp et al, 2016Zemp et al, , 2018. DC is defined in the systemic-transactional model of stress (Bodenmann, 1995b(Bodenmann, , 1997(Bodenmann, , 2005 as the interpersonal process through which couples jointly cope with stress.…”
mentioning
confidence: 99%